Three-dimensional computed tomographic angular measurements of the canine tibia using a bone-centered coordinate system - Brühschwein, Andreas; Schmitz, Bronson; Zöllner, Martin; Reese, Sven; Meyer-Lindenberg, Andrea (Frontiers in Veterinary Science, 2023)
Canine tibial alignment is determined by two-dimensional angular measurements, and tibial torsion is challenging. Aim of the study was the development and evaluation of a CT technique to measure canine tibial varus and torsion angles independent from positioning and truly three-dimensional. A bone-centered 3D cartesian coordinate system was introduced into the CT-scans of canine tibiae and aligned with the anatomical planes of the bone based on osseous reference points. Tibial torsion, and varus (or valgus) angles were calculated based on geometric definition of projection planes with VoXim® medical imaging software using 3D coordinates of the reference points. To test accuracy of the tibial torsion angle measurements, CT scans of a tibial torsion model were performed in 12 different hinge rotation setups ranging from the normal anatomical situation up to +/ 90° and compared to goniometer measurements. Independency of tibial positioning on the CT scanner table was evaluated in 20 normal canine tibiae that were scanned in a position parallel to the z-axis and two additional off-angle double oblique positions having 15° and 45° deviation in direction of the x- and y-axes. Angular measurements in oblique positions were compared with the normal parallel position by subtraction. Precision was tested using clinical CT scans of 34 canine patients with a clinical diagnosis of patellar luxation. Accuracy testing in the tibial torsional deformity model revealed a difference of 0.2° demonstrated by Passing-Bablok analysis and Bland-Altman-Plots. Testing for independency from tibial positioning resulted in mean differences less than 1.3°. Precision testing in clinical patients resulted in coefficients of variation for repeated measurements of 2.35% (intraobserver agreement) and 0.60% (interobserver agreement) for the tibial torsion angle, and 2.70% (intraobserver agreement) and 0.97% (interobserver agreement) for the tibial varus (or valgus) angle. The technique is lacking determination of bone deformities in the sagittal plane, and demonstration of accuracy in severe complex bone deformities in multiple planes. In conclusion, we developed a method to measure canine tibial torsional and varus or valgus deformities, that calculates in 3D space, and we demonstrated its accuracy in a torsional deformity model, and its precision in CT data of clinical patients.